Organizational behaviour - Buchanan, David A. (London Pearson, 2013)
Buchanan and Huczynski bring their well-known and successful brand of critical thinking, social science underpinning, and visual appraisal to bear in this comprehensive introduction to organizational behaviour. This highly successful textbook has been substantially updated to include the latest research, most relevant contemporary issues and up-to-date practical examples. Organizational Behaviour involves the reader directly, placing them in the position of decision-making and problem-solving manager, inviting them to see the reality behind an organizational image, and encouraging the reader to make comparisons with well-known scenes in film and literature.
Includes bibliographical references Index
Keywords: Organizational behavior